Diagnosis and management of tubo‐ovarian abscesses. (28th January 2018) - Munro, Kirsty; Gharaibeh, Asma; Nagabushanam, Sangeetha; Martin, Cameron
Abstract : Key content: Tubo‐ovarian abscesses represent a severe form of pelvic inflammatory disease and carry high morbidity. Diagnosis is made by combining the clinical picture (fever, pelvic pain and pelvic adnexal mass) with raised inflammatory markers and radiological findings demonstrating an abscess. Initial management with intravenous antibiotics may not be successful. Surgical intervention may be indicated but the optimal timing is not clear and image‐guided drainage can be a possible alternative to surgery. Surgery may be conservative or involve pelvic clearance and will depend on the clinical situation. Learning objectives: To be able to recognise and initiate prompt treatment of pelvic inflammatory disease and tubo‐ovarian abscesses. To understand appropriate antibiotic treatment and/or radiological drainage. To be able to identify indications for timely surgical intervention and explore the optimal surgical approach of laparoscopic versus open surgery. Ethical issues: Delays in treatment may have adverse effects on future fertility. Who is appropriate for fertility‐preserving treatment?